2019
DOI: 10.3390/plasma2010004
|View full text |Cite
|
Sign up to set email alerts
|

Generators of Atmospheric Pressure Diffuse Discharge Plasma and Their Use for Surface Modification

Abstract: Studies of the properties of runaway electron preionized diffuse discharges (REP DDs) and their possible use have been carried out for more than 15 years. Three experimental setups generating a low-temperature atmospheric-pressure plasma and differing in the geometry of a discharge gap were developed. They allow the treatment of surfaces of different materials with an area of several tens of square centimeters. A diffuse discharge plasma was formed in the pulse–periodic mode by applying negative voltage pulses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The flat electrode (anode) is exposed to reactive species and optical radiation resulting from ionization and excitation in plasma, as well as high-energy electrons and X-rays caused by their deceleration. Some results from modifying the surfaces of various materials with this kind of plasma are presented in [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flat electrode (anode) is exposed to reactive species and optical radiation resulting from ionization and excitation in plasma, as well as high-energy electrons and X-rays caused by their deceleration. Some results from modifying the surfaces of various materials with this kind of plasma are presented in [15].…”
Section: Introductionmentioning
confidence: 99%
“…We believe that the damage to the anode surface mentioned in papers [16,[19][20][21][22] is due to the relatively long duration of both the voltage pulse itself and its rise time, which leads to discharge constriction. Our previous studies [15,24] have shown that local damage to the surface of a flat electrode is only observed when anode spots are formed, which occur when the interelectrode distance decreases or the energy input increases. A discharge mode in which uniformity is improved and there is no local damage to the anode is implemented with an increase in the gap width as well as a decrease in the amplitude or duration of the applied voltage pulse.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of such discharges is accompanied by the generation of runaway electrons and X-rays [1,3,6], and the discharges themselves find practical applications in various scientific and technical fields. Thus, the diffuse discharge formed in the gap with a cathode with a small radius of curvature is used to clean surfaces from carbon, as well as to improve adhesion, to oxidize, and to harden a surface of various metals [7]. The use of pointed cathodes makes it possible to form diffuse discharges in pressured gases in a wide range of experimental conditions [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…[1,3,6], and the discharges themselves find practical applications in various scientific and technical fields. Thus, the diffuse discharge formed in the gap with a cathode, which had a small radius of curvature, was used to clean surfaces from carbon, improve adhesion, oxidize and harden the surface of various metals [7]. The use of point cathodes makes it possible to form diffuse discharges in pressured gases in a wide range of experimental conditions [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%